2020
DOI: 10.1002/ajp.23223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rainfall on sleeping site choice by a group of anubis baboons (Papio anubis)

Abstract: For diurnal nonhuman primates, shifting among different sleeping sites may provide multiple benefits such as better protection from predators, reduced risk of parasitic infection, and closer proximity to spatially and temporally heterogeneous food and water. This last benefit may be particularly important in sleeping site selection by primates living in savanna‐woodlands where rainfall is more limited and more seasonally pronounced than in rainforests. Here, we examined the influence of rainfall, a factor that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We report a rare observation of three troops of olive baboons utilizing electrical transmission pylons as sleeping sites in Laikipia County, Kenya. Usually, in this landscape, tall Acacia trees and rocky cliffs are predominantly selected as sleeping sites by baboons (Bidner et al, 2018;Hamilton, 1982;Suire et al, 2020). Typically, tall A. xanthophloea with vines and branches overhanging rivers remain preferred sleeping site (Bidner et al, 2018;Isbell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We report a rare observation of three troops of olive baboons utilizing electrical transmission pylons as sleeping sites in Laikipia County, Kenya. Usually, in this landscape, tall Acacia trees and rocky cliffs are predominantly selected as sleeping sites by baboons (Bidner et al, 2018;Hamilton, 1982;Suire et al, 2020). Typically, tall A. xanthophloea with vines and branches overhanging rivers remain preferred sleeping site (Bidner et al, 2018;Isbell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While other primate species have been observed using anthropogenic structures such as rooftops and electricity poles (Bracken et al., 2021 ; Brotcorne et al., 2014 ; Hoffman & O'Riain, 2012 ), this behavior has not been reported before in Laikipia, Kenya (Bidner et al., 2018 ; Butynski & De Jong, 2014 ; Danish & Palombit, 2014 ; Isbell et al., 2017 ; Matsumoto‐Oda, 2015 ; Strum, 2005 ; Suire et al., 2020 ). For example, at Mpala Research Centre in Laikipia, despite the availability of pylons from the same transmission line within known baboon home ranges, baboons still use cliffs and tall trees as their preferred sleeping sites (Bidner et al., 2018 ; Isbell et al., 2018 ; Suire et al., 2020 ) and have yet to be observed using pylons. We document olive baboons using high‐tension electrical transmission towers (hereafter “pylons”) recently installed to transmit power between Kenya and Ethiopia (EEPCO & KETRACO, 2012 ) as sleeping sites, and we discuss the implications of this behavior for understanding natural sleeping site preferences.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Olive baboons (Papio anubis, hereafter ' baboon') use secure and naturally-occurring sleeping sites such as tall trees and cliffs as an anti-predator strategy while sleeping (Hamilton, 1982;Isbell et al, 2018). In addition to predation risk, parasite infestation and fecal-matter load within sleeping sites can influence their frequency of use (Hausfater and Meade, 1982), and the limited availability of good quality sites is generally thought to regulate baboon distribution and group sizes (Cheney et al, 2003;Markham et al, 2015;Suire et al, 2020). While other primate species have been observed using anthropic structures such as rooftops and electricity poles (Bracken et al, 2021;Brotcorne et al, 2014;Hoffman and O'Riain, 2012;Sarker et al, 2005), this behavior has not been observed in long-term baboon studies in Laikipia, Kenya (Bidner et al, 2018;Butynski, and Jong, 2014;Danish and Palombit, 2014;Isbell et al, 2017;Matsumoto-Oda, 2015;Strum, 2005;Suire et al, 2020).…”
Section: Introductionmentioning
confidence: 99%